Expenditure pattern analysis of cultural tourists at World Heritage Sites: an empirical evidence based on CHAID analysis - Serra, Jaime (2017)
Nowadays, World Heritage Sites (WHS) have been facing new challenges, partially due to a different tourism consumption patterns. As it is highlighted in a considerable amount of studies, visits to these sites are almost justified by this prestigious classification and motivations are closely associated with their cultural aspects and quality of the overall environment (among others, Marujo et al, 2012). However, a diversity of tourists’ profiles have been underlined in the literature. Starting from the results obtained in a previous study about cultural tourists’ profile, conducted during the year 2009 in the city of Évora, Portugal, it is our intend to compare the results with a recent survey applied to the visitors of the same city. Recognition of Évora by UNESCO in 1986 as “World Heritage” has fostered not only the preservation of heritage but also the tourist promotion of the town. This study compares and examined tourists’ profile, regarding from the tourists’ expenditure patterns in Évora. A total of 450 surveys were distributed in 2009, and recently, in 2015, the same numbers of surveys were collected. Chi-squared Automatic Interaction Detection (CHAID) was applied to model consumer patterns of domestic and international visitors, based on socio demographic, trip characteristics, length of stay and the degree of satisfaction of pull factors. CHAID allowed find a population classification in groups that able to describe the dependent variable, average daily tourist expenditure. Results revealed different patterns of daily average expenditure amongst the years, 2009 and 2015, even if primarily results not revealed significant variations in socio-demographic and trip characteristics among the visitors’ core profile. Local authorities should be aware of this changing expensive behavior of cultural visitors and should formulate strategies accordingly. Policy and managerial recommendations are discussed.